Legal Certainty Regarding the Cancellation of Property Rights Certificates From the Perspective of Land Registration Objectives (Case Study of Property Rights No. 55 in Tanjung Pasir Village, Tangerang Regency) - Amril, Amril; Dwisvimiar, Inge; Agustina, Rani Sri (Fox Justi : Jurnal Ilmu Hukum, 2025)
Problems of a plot of land are often associated with problems of ownership of the plot of land. The state guarantees legal certainty in the ownership of land rights that have been regulated in Government Regulation Number 24 of 1997 concerning Land Registration. The problem discussed is regarding ownership between the Deed of Sale and Purchase and the double certificate, hence the cancellation of the Certificate of Ownership Rights Number 55 of Tanjung Pasir Village, in the name of Etjah. The research method used is empirical with a normative approach. The data sources used are primary data and secondary data. Primary data is data obtained from parties related and involved in this study, namely the Tangerang Regency Land Office, the Tangerang Regency Land Deed Official, the owner of the Land Ownership Certificate No. 55/Tanjung Pasir. While secondary data is data obtained from literature studies. Based on the results of the study on the legal certainty of land rights, the Certificate of Ownership Number 55/Tanjung Pasir was first recorded in the name of Etjah which was transferred to Suha Bin Eneng and then transferred to Andre Lukas Simon. The root of the problem is that Vreddy is the party claiming the Customary Land Ownership Rights, so Vreddy filed a lawsuit against the object of the State Administrative Law (TUN) lawsuit. Thus, the Decision of the Serang State Administrative Court Number 10/G/2021/PTUN/SRG. dated June 30, 2021 in accordance with Article 110 of Law 51 of 2009 concerning the second amendment to Law Number 5 of 1986 concerning State Administrative Courts, the losing party in this case is sentenced to pay all court costs incurred in two levels of court, for which the appeal level is determined as stated in the verdict.